THE EFFECT OF AMORPHOPHALLUS MUELLERI BLUME AND MORINGA OLEIFERA L LEAVES ON BODY WEIGHT, FEED INTAKE, AND HEPATIC HISTOPATHOLOGY IN MICE - LAKSMITAWATI, DIAN RATIH; MARWATI, UMI; SUMIYATI, YATI; PRATAMI, DIAH KARTIKA; SARI, INTAN PERMATA (International Journal of Applied Pharmaceutics, 2021)
Objective: This study aims to determine the effect of Amorphophallus muelleri Blume and Moringa oleifera L leaf on body weight, food intake, and hepatic histopathology in mice. Methods: The mice were divided into five groups according to their diet, which includes porang, wheat, porang-moringa, wheat-moringa, and control diet. Each group consists of 5 males and 5 females, which were fed for 28 d, and then analyzed for their body weight, total food intake, alanine aminotransferase (ALT) as well as aspartate aminotransferase (AST) levels in plasma, and hepatic histopathology. Results: The result showed that the group of porang and porang-moringa has lower body weight and feed intake, which is significantly different compared to the others. Furthermore, an increase was observed on plasma AST/ALT activities in 30% porang and 20% porang-moringa group. Also, one of the mice of porang group has inflammatory cell infiltration (++) on histopathology results. Conclusion: It was therefore concluded that feeding containing porang causes low food consumption. Furthermore, weight loss increases AST/ALT and leukocyte infiltration even though a mouse consistently deteriorates.